2017
DOI: 10.1002/ajcp.12136
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Family Unification Housing Vouchers on Child Welfare Outcomes

Abstract: This study addresses whether providing housing vouchers through the Family Unification Program (FUP) to families involved in the child welfare system reduces child maltreatment and the need for child welfare services. The study uses child welfare administrative data on 326 children in Portland, Oregon, and 502 children in San Diego, California from the point at which their families were referred to the program through 18 months post-referral. Using a quasi-experimental waitlist comparison design, probit regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…More recent, rigorous evaluations show mixed effects on child welfare outcomes. A quasi-experiment conducted in San Diego and Portland found that families who received FUP showed lower rates of out-of-home placement over 18 months compared to families who received usual child welfare services (Pergamit, Cunningham, & Hanson, in press). However, receipt of FUP vouchers also related to increases in maltreatment re-reports for families working toward reunification, and no differences appeared in rates of out-of-home placement or reunification among families who received FUP versus similar families who received child welfare services as usual.…”
Section: Policy Initiatives and Emerging Evidence On Housing Intervenmentioning
confidence: 99%
See 2 more Smart Citations
“…More recent, rigorous evaluations show mixed effects on child welfare outcomes. A quasi-experiment conducted in San Diego and Portland found that families who received FUP showed lower rates of out-of-home placement over 18 months compared to families who received usual child welfare services (Pergamit, Cunningham, & Hanson, in press). However, receipt of FUP vouchers also related to increases in maltreatment re-reports for families working toward reunification, and no differences appeared in rates of out-of-home placement or reunification among families who received FUP versus similar families who received child welfare services as usual.…”
Section: Policy Initiatives and Emerging Evidence On Housing Intervenmentioning
confidence: 99%
“…Vouchers represent a key component of housing interventions delivered across service systems; evidence clearly demonstrates their value for families entering homeless shelters (Gubits et al, 2015; Shinn et al, in press). Although effect sizes appear more modest, permanent housing shows promise in keeping families together among those already under investigation (Fowler, Brown, et al, 2017b; Pergamit et al, in press). The value added remains uncertain when housing vouchers are used to promote reunification or combined with additional case management (Farrell et al, 2010; Pergamit et al, in press; Rog et al, in press).…”
Section: Evidence In Context Of Scale-upmentioning
confidence: 99%
See 1 more Smart Citation
“…This crisis in affordable housing results in 75% of ELI renter households in 2014 spending more than half of their income on rent and utilities. As discussed by several authors in this issue (Fowler & Schoeny, ; Pergamit, Cunningham & Hanson, ; Shinn, Grown & Gubits, ), targeting housing vouchers to families with the highest need is important; the reality, however, is that current funding for housing vouchers is insufficient to meet the need. The number of families with children who receive federal housing subsidies has fallen by 13% since 2004, marking 2016 as its lowest point in more than a decade (Mazzara, Sard & Rice, ).…”
Section: Translating Research To Housing Policymentioning
confidence: 99%
“…Results from the San Diego and Portland sites show that families receiving a FUP voucher were less likely to be re-reported to CPS than other families, but other outcomes such as reduced days to reunification or reduced likelihood of a substantiated re-report to CPS were not significant or inconsistent across sites (Pergamit, Cunningham, & Hanson, 2017). Several factors may contribute to the program’s modest impact estimates, including implementation issues in appropriately targeting families (Cunningham et al, 2015), lack of an experimental design, and the relatively small number of vouchers issued by the program.…”
Section: Introductionmentioning
confidence: 99%